Pemberian Jus Mentimun untuk Menurunkan Tekanan Darah Pada Penderita Hipertensi di Desa Manunggang Jae Kecamatan Padangsidimpuan Tenggara Kota Padangsidimpuan - Daulay, Nanda Masraini (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
The prevalence of hypertension has increased over the past few decades and has become a major health problem because awareness of treatment and hypertension control levels is still very low (Li Y, Yang L et al, 2017). In principle, there are two types of therapy that can be done to treat hypertension, namely pharmacological and non-pharmacological therapies. One of the non-pharmacological therapies is the provision of cucumber juice which can lower blood pressure (Tjiptaningrum & Erhadestria, 2016). The demonstration of cucumber juice is aimed at lowering the blood pressure of hypertensive sufferers and training people in lowering blood pressure in a non-pharmacological way, namely giving cucumber juice independently at home. The activities carried out consisted of measuring blood pressure, demonstration of cucumber juice making, and health education about the benefits of cucumber in reducing blood pressure. The number of participants was 25 people with hypertension. The results of this activity found that 20 people (80%) with hypertension experienced a decrease in blood pressure. The community seemed enthusiastic and able to practice making cucumber juice. PKM on demonstration of non-pharmacological therapy to lower blood pressure can be carried out routinely with different types of complementary therapies such as herbal therapy in lowering blood pressure.